Identification of a conserved gene family with an essential role in Leishmania parasite–insect vector adhesion - Barrack O. Owino; Ryuji Yanase; Katerina Pruzinova; Helen Farr; Yaimie Lopez; Alan O. Marron; Sue Vaughan; Petr Volf; Jack D. Sunter (Proceedings of the National Academy of Sciences, 2026)
Adhesion to tissues and surfaces is used by pathogens to avoid clearance, maintain infections, and facilitate transmission. An important example is the adhesion of the Leishmania parasite to the stomodeal valve of its insect vector, the sand fly, which is important for life cycle progression, and occurs through its flagellum via a cytoskeletal adhesion complex. While three essential kinetoplastid-insect adhesion proteins (KIAPs) are known, the overall proteome of the adhesion complex is obscure. Using TurboID-tagged KIAP3 combined with proteomics and light microscopy, we have identified additional proteins associated with the adhered flagellum, including multiple members of the Adhesion Related NTPase-like Domain (ARND) family, of which the canonical member is KIAP4, described here. Phylogenetic analysis of the ARND family showed it is conserved across the kinetoplastids, and we demonstrate that Trypanosoma congolense paralogs localize to the adhered flagellum in that parasite. Deletion of KIAP4 severely impaired haptomonad adhesion, with the mutant parasites unable to colonize the sand fly stomodeal valve. Our work provides details of the molecular machinery essential for vector colonization and shows that these proteins have a conserved function in other kinetoplastid parasites.